Assessment of Facial Asymmetry in Orthognathic Patients. (2nd January 2019) - Gibson, Clara; Noar, Joseph
Abstract : Discrepancies between dental and facial midlines are not uncommon and these may have a dental or a skeletal cause. When planning orthognathic surgery, a decision must be made whether to accept or correct these. This paper presents a simple technique that uses graph paper to evaluate any midline discrepancies as an aid to pre-treatment discussion and explanation with the patient. CPD/Clinical Relevance: Accurate diagnosis of the clinical problem and complete patient understanding of the situation are imperative, both for informed consent and for a favourable treatment outcome. Tracing of a posterior-anterior cephalogram on graph paper can aid treatment planning and patient comprehension.